Evaluation of land spatial suitability in the Guangdong-Hong Kong-Macao Greater Bay Area - Li, Changlong; Li, Xuxin; Sun, Bin; Weng, Kaican; Zhan, Zhiyu; Yang, Chonghao (Frontiers in Sustainable Cities, 2025)
The rapid urbanization and industrialization of the Guangdong-Hong Kong-Macao Greater Bay Area (GBA) pose a severe challenge for rational land use. This study presents a multi-factor land-use suitability assessment system with economic, social, and environmental dimensions. System reliability and stability are confirmed by a Cronbach’s α coefficient (>0.7). We innovatively integrate the PS-DR-DP model with the Monte Carlo and Markov models. The Markov model analyzes transition probabilities between different land capacity states. The Monte Carlo method quantifies key parameter uncertainties through extensive random sampling, while the Markov chain-Monte Carlo approach dynamically evaluates and predicts land capacity. From 2002 to 2022, overall GBA land-population carrying capacity is stable above 0.6 and keeps rising, reflecting improved regional land capacity and successful coordinated development. However, the forecast results indicate that land capacity will first increase and then decrease between 2023 and 2042, with most cities reaching a peak carrying capacity (S-value approaching or exceeding 2) in 2027. This peak is followed by a projected decline, and by 2042, the overall land capacity may drop to around 0.5, signaling a significant long-term risk of overload. If current development trends continue, the region faces significant long-term risks of declining carrying capacity, particularly if the transition to a sustainable, innovation-driven economy is not managed effectively. This highlights the profound challenge of balancing economic growth, urbanization, and ecological protection. These recommendations offer scientific evidence and decision-making support for sustainable GBA development.